Respiratory Syncytial Virus (RSV): Virologi, Patogenesis, Respon Imun, dan Vaksin Pada Dewasa - Resti H. Lestari; Fariz Nurwidya; Anis Karuniawati (MEDICINUS, 2025)
Respiratory syncytial virus (RSV) is classified within the Pneumoviridae family, genus Orthopneumovirus. RSV is a single-stranded, negative-sense RNA virus and has two genotypes, A and B. It is primarily associated with lower respiratory tract infections, including bronchiolitis and bronchopneumonia, and is a common cause of hospitalization in infants, elderly individuals, and immunocompromised patients. RSV also has the potential to become systemic infection. Symptoms of RSV infection, such as fever, cough, sore throat, and runny nose, are usually mild in adults. However, in some cases, especially for specific high-risk individuals, the infection can become severe enough to require hospitalization, and complications may lead to death. Understanding the pathogenesis and immune response to RSV are crucial for recognizing the virus’s effects and potential risks. This literature review covers the virology, pathogenesis, immune response, and recent advancements in RSV vaccine development in adult populations. Comprehensive knowledge of RSV is essential for developing effective prevention and treatment strategies.